SOME ASSESSMENTS OF THE PUBLICATION ACTIVITY OF SCIENTISTS OF THE KUBAN STATE UNIVERSITY OF PHYSICAL CULTURE, SPORT AND TOURISM. - Shegelman I. R., Kirilina V. M., Vasilyev A. S. (Pedagogy and psychology: development prospects, 2019)
according to the knowledge base of the Russian scientific citation index, some estimates of the publication activity of scientists of the Kuban State University of Physical Culture, Sports and Tourism.
Keywords: физическая культура и спорт; патент; индекс Хирша; цитирование; публикации; база знаний; publications; knowledge base; patent; physical education and sport; Hirsch index; citation